Gorkha (Nepal) earthquake of April 25, 2015: Actual damage, retrofitting measures and prediction by RVS for a few typical structures. Issue 89 (October 2016) - Dutta, Sekhar Chandra; Nayak, Sanket; Acharjee, Gokul; Panda, Sarat Kumar; Das, Pranab Kumar
Abstract: This study is an attempt to underline the lack of preparedness and the nature of immediate further measures to be taken for facing a moderate earthquake in Indian subcontinents. Surprisingly, moderate to severe damage was noticed in structures located in hundreds of kilometres away from epicentre during last Gorkha earthquake. In this context, the present study makes an effort to validate a proposed modified rapid visual screening schemes for low cost houses frequently available in India. This may be used extensively for quick vulnerability assessment of a locality. Examples of retrofitting measures for typical buildings presented in this study may be useful for upgrading the valuable structures. Thus this study may be helpful for quick vulnerability assessment and adopting retrofitting measures for identified structures for earthquake prone developing countries. Highlights: Poor seismic performance of non-engineered structures are reported. Seismic vulnerability assessment of various types of structures are discussed. Different strengthening techniques are suggested. Modified RVS strategy is used. A direction towards earthquake preparedness is attempted to be provided.